Pengaruh Kompetensi SDM, Moralitas, Whistleblowing dan SPI Terhadap Pencegahan Fraud Dalam Pengelolaan Keuangan Desa - Jayanti, Luh Sri Isa Dewi; Suardana, Ketut Alit (E-Jurnal Akuntansi; Vol 29 No 3 (2019)DO - 10.24843/EJA.2019.v29.i03.p16, 2019)
The purpose of this study was to empirically examine the effect of human resource competence, morality, whistleblowing and internal control systems on fraud prevention in partial village financial management. This research was conducted in 27 Dinas Villages in Denpasar City using total or census methods. Respondents used were 108 people. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that human resource competence, morality, whistleblowing, and internal control systems have a positive effect on fraud prevention in village financial management. This means, with the competence of human resources, good morality and a strong internal control system, it can prevent fraud in the management of village finances. Keywords : Human Resource Competence; Morality; Whistleblowing; Internal Control System; Fraud.